KORELASI KETERAMPILAN MEMAHAMI TEKS CERPEN DENGAN KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMA NEGERI 1 ENAM LINGKUNG - Suci, Diana; Gani, Erizal; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT The aimed of this researchwas to describe the student’s correlation of comprehension skill on short story text with skil of writing the short story text at class XI SMA Negeri 1 Enam Lingkung. The subject of this research was the second grade students of class XI SMA Negeri 1 Enam Lingkung with sample of 34 people. The kind of this research is the quantitative with descriptive method. The data of this research are gotten by two kind of test. The test are multiple choice test in order to collect  the data of comprehension skill on short story text, the second is the student’s woerksheet test in order to collect the data of writing the short story text. Based on the results of data analysis can be concluded that; first, the student’s comprehension skill on comprehend the text are in good qualifying (85.06). Second, the student’s writing skill in writing the short story text class XI student of class XI SMA Negeri 1 Enam Lingkung are in good qualifying (77.33). Third, there is a significant correlation between student’s comprehension skill an writing skillin comprehending and witing short story text of the second grade students at class XI SMA Negeri 1 Enam Lingkung that is 0.784 it  can be proved by the t-count > t table (7.15> 1.70) in level 95%. Kata kunci: korelasi, memahami teks cerpen, menulis teks cerpen